Research on the influence of payment methods on the control of medical insurance expenses—Based on empirical analysis of double difference - Luo, Juan; Wang, Shuxin; Dan, Lulu; Zhang, Rui; Bi, Liang (Frontiers in Public Health, 2022)
Background The medical insurance system is constantly reformed and optimized. In order to control the cost of medical insurance funds, the medical insurance payment method has been reformed. The reform of the payment method can effectively control the medical insurance expenses. Method In this paper, the annual data of 27 provinces from 2013 to 2017 were selected, and the cost control effect of the dual difference (DID) model of medical insurance payment method was analyzed. Results The study found that the effect of the pilot reform of medical insurance payment mode was in line with the policy objectives and achieved the effect of cost control to a certain extent. Conclusion The failure to significantly reduce the growth rate of the expenditure of medical insurance funds is not ideal to curb the excessive growth of health insurance funds. Therefore, strengthening the control of medical expenses, improving the control of medical insurance fund fees through the reform of payment methods are the effective ways to strengthen the control of medical insurance funds.